EFEKTIVITAS ANALISIS JABATAN PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) SAPTAWA POVINSI LAMPUNG - Dewi, Rika; Farida, Ida (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2022)
Based on Article 117 paragraph (1) of Law Number 43 of 1999 concerning Amendments to Law Number 8 of 1874 concerning the Principles of Personnel, it is determined that civil servants are appointed in positions and ranks. To ensure objectivity, transparency, and conformity between the job demands and the employee who will occupy the position, it is necessary to carry out a job analysis. The results of the job analysis in the form of job information can be used for institutional, management, and staffing purposes. In this study, researchers conducted research on the effectiveness of Job Analysis in the Indonesian Civil Servant Cooperative (KPRI) SAPTAWA, Lampung Province. The method used in this research is a qualitative research method with a descriptive research design. The results of this study are from various indicators used to measure the achievement of goals, acquisition of resources, internal processes and satisfaction of strategic constituencies. From the points of achievement of the effectiveness indicators, the researcher concludes that the Job Analysis at the SAPTAWA Province Employee Cooperative of the Republic of Indonesia (KPRI) in Lampung Province has been effective and has made the quality of service provided to customers and the internal working atmosphere well done. The supporting factor in the implementation of this job analysis is a clear legal basis, then the inhibiting factor in the job analysis at the Indonesian Civil Service Cooperative (KPRI) SAPTAWA Lampung Province is the ideological difference between employees. Keywords: Effectiveness, Job Analysis, Cooperatives